Effect of CYP3A4∗1G and CYP3A5∗3 Polymorphisms on Pharmacokinetics and Pharmacodynamics of Ticagrelor in Healthy Chinese Subjects - Liu, Shuaibing; Shi, Xiangfen; Tian, Xin; Zhang, Xiaojian; Sun, Zhiyong; Miao, Liyan (Frontiers in Pharmacology, 2017)
Ticagrelor is the first reversible, direct-acting, potent P2Y12 receptor antagonist in management of acute coronary syndromes. It is rapidly absorbed and extensively metabolized. AR-C124910XX, the major active metabolite, antagonizes the P2Y12 receptor at approximately equal potency. The metabolism of ticagrelor to AR-C124910XX involves CYP3A4 and 3A5. CYP3A polymorphisms have been well documented and CYP3A4*1G (g.20230G>A, rs2242480) and CYP3A5*3 (g.6986A>G, rs776746) alleles are the most important SNPs in Chinese. Genetic differences in CYP3A4 and CYP3A5 expression in human volunteers and patients might affect the clearance of ticagrelor or AR-C124910XX in vivo resulting in subsequent variable patient response. Thus, this study is designed to explore the effects of CYP3A4*1G and CYP3A5*3 polymorphisms on the pharmacokinetics and pharmcodynamics of ticagrelor in healthy Chinese subjects. The results indicated that the CYP3A4*1G polymorphism significantly influenced the pharmacokinetics of AR-C124910XX, and it may be more important than CYP3A5*3 with respect to influencing ticagrelor pharmacokinetics by increasing CYP3A4 activity. However, the significant effect of CYP3A4*1G polymorphism on AR-C124910XX plasma levels did not translate into detectable effect on inhibition of platelet aggregation. Therefore, it seems not necessary to adjust the dosage of ticagrelor according to the CYP3A4 or 3A5 genotype.